Safety and efficacy of a feed additive consisting of inactivated selenised yeast (Saccharomyces cerevisiae CCTCC M 2022402) for all animal species (Phytobiotics Futterzusatzstoffe GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of the selenised yeast (inactivated) Saccharomyces cerevisiae CCTCC M 2022402 (Plexomin® Se 3000, available in two forms: ‘granules’ and ‘micro’) as a nutritional feed additive for all animal species. Based on a tolerance–efficacy trial, the FEEDAP Panel concluded that the additive is safe for chickens for fattening at proposed conditions of use and this conclusion can be extrapolated to all animal species. In the absence of deposition data in all animal species and products, the FEEDAP Panel cannot conclude on the safety for the consumer. Plexomin® Se 3000 (granules) is dust‐free; therefore, the exposure through inhalation is unlikely. Plexomin® Se 3000 (micro) presents a risk by inhalation. Both forms of the additive (granules and micro) are considered as respiratory sensitisers. Due to the lack of data, no conclusions can be drawn on the dermal and eye irritation potential of Plexomin® Se 3000 (granules). Plexomin® Se 3000 (micro) is not irritant to the skin and the eyes. No conclusions can be drawn on the potential of both forms of the additive to be dermal sensitisers. The use of the additive in animal nutrition is considered safe for the environment. The additive is an efficacious source of selenium in feedingstuffs for all animal species.